Determination of compliance with UK and EU air quality objectives from high-resolution pollutant concentration maps calculated using ADMS-Urban. (1st January 2001) - Carruthers, D.J.; Dickson, P.; McHugh, C.A.; Nixon, S.G.; Oates, W.
The main features and functionality of the urban air quality version of ADMS (ADMS-Urban) have been presented at previous Harmonisation Workshops. The system has now been set up and applied to air quality management, decision support and air quality forecasting in a number of major cities in Europe and beyond, including London. Key recent developments of the system include a regional chemistry model, links to real time and forecasted meteorological data and an advanced emission database (EMIT) for calculating current and projected road traffic emissions from different diurnal traffic flow profiles and vehicle mixes. In this study, we consider a detailed analysis of the impact of various road traffic measures, such as high maintenance, low emission zones, increased bus use, reduced traffic flow etc, applied to the Birmingham metropolitan area. We show the impact on compliance or otherwise with the UK National Air Quality Strategy objectives and the proposed EU air quality daughter objectives. We also present high-resolution maps of calculations for London of predictions based on projected vehicle emission changes for the years 2004 and 2005. Both these sets of results are being used by policymakers in local authorities in the preparation of their air quality management plans.